Mobile compact 1H NMR spectrometer promises fast quality control of diesel fuel. (1st September 2017) - Killner, M.H.M.; Danieli, E.; Casanova, F.; Rohwedder, J.J.R.; Blümich, B.
Graphical abstract: Highlights: Bench top NMR spectrometer to determine different quality parameters of diesel fuel. 9 important diesel fuel quality parameters determined in less than 1 min. Similar results compared to reference methods applied nowadays. Low field NMR spectroscopy as a powerful technique for police control of diesel fuel. Abstract: To address the need for fast quality control of diesel fuel, this study introduces a compact 1 H NMR spectrometer to develop Partial Least Squares (PLS) regression models for rapidly determining several quality parameters of diesel fuel such as specific gravity, cetane number, flash point, and distillation temperatures to 10% and 50% of recovery. For all these quality parameters, the developed models showed margins of error better or comparable than reference analytical techniques. The compact NMR spectrometer was also applied for determining biodiesel content (methyl- and ethyl esters) in diesel fuel by using a univariate calibration curve. For all tested commercial diesel fuel samples, this new tool generated comparable results, within the tolerable margin of error, to those obtained with Mid-IR as a reference technique. Operation of the compact low-field NMR spectrometer is simple and fast: no sample pre-treatment or dilution in deuterated solvents is required, and the single-scan measurements take only 15 s per spectrum.